Gut Microbiota-Related Inflammation Factors as a Potential Biomarker for Diagnosing Major Depressive Disorder - Bai, Shunjie; Bai, Huili; Li, Detao; Zhong, Qi; Xie, Jing; Chen, Jian-jun (Frontiers in Cellular and Infection Microbiology, 2022)
Objective: Although many works have been done, the objectively measured diagnostic biomarkers are not available. Thus, we conducted this study to identify potential biomarkers for objectively diagnosing depression and explore the role of gut microbiota in the onset of depression. Methods: Major depressive disorder (MDD) patients (n=56) and demographic data-matched healthy controls (HCs) (n=56) were included in this study. The gut microbiota in fecal samples and inflammation-related factors in serum were measured. Both univariate and multivariate statistical analyses were performed to identify the differential gut microbiota and inflammation-related factors. Results: Finally, 46 differential operational taxonomic units (OTUs) (60.9% OTUs belonging to Firmicutes) and ten differential inflammation-related factors were identified. Correlation analysis showed that there were significant correlations between 14 differential OTUs (9 OTUs belonging to Firmicutes and 5 OTUs belonging to family Lachnospiraceae under Firmicutes) and seven differential inflammation-related factors. Meanwhile, 14 differential OTUs (9 OTUs belonging to Firmicutes and 5 OTUs belonging to family Lachnospiraceae under Firmicutes) and five differential inflammation-related factors (adiponectin, apolipoprotein A1, alpha 1-antitrypsin, neutrophilicgranulocyte count/white blood cell count and basophil count) were significantly correlated to depression severity. A panel consisting of these five differential inflammation-related factors could effectively diagnose MDD patients from HCs. Conclusions: Our results suggested that Firmicutes, especially family Lachnospiraceae, might play a role in the onset of depression via affecting the inflammation levels of host, and these five differential inflammation-related factors could be potential biomarkers for objectively diagnosing MDD.